Analisis Pengaruh Pergantian Manajemen, Komite Audit, Financial Distress, Reputasi Auditor, Audit Fee, terhadap Auditor Swithcing - Destin Alfianika Maharani; Karunia Zuraidaning Tyas; Shella Rizqi Amelia; Fitriyanti, Fitriyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study focuses on analyzing the factors influencing auditor switching in telecommunications companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period, by examining the variables of management turnover, audit committee, financial distress, auditor reputation, and audit fees. The study was conducted using a quantitative approach utilizing secondary data in the form of annual financial reports. The sample size was determined using a purposive sampling technique for 55 companies. Auditor switching served as the dependent variable, measured by a dummy variable, while the other five variables served as independent variables. The analysis results indicate that none of the independent variables significantly influenced auditor switching decisions. This suggests that auditor switching decisions in companies are more influenced by strategic factors, such as the company's need to obtain audit services that better align with its business vision and auditor competency, which is considered capable of maintaining the credibility of financial reports. These findings emphasize the importance of a continuous relationship between auditors and clients as part of efforts to maintain the quality, consistency, and independence of the resulting audit. The practical implication of this study is that companies need to prioritize professionalism, audit quality, and long-term partnerships with auditors, rather than solely considering internal factors such as management structure or financial pressure. From a regulatory perspective, this research provides important input for strengthening regulations and oversight regarding audit quality and auditor independence, rather than solely focusing on auditor switching frequency. Thus, this study expands the literature on auditor switching dynamics and confirms that audit success is determined more by the quality of relationships and competence than by internal technical factors alone.